Experimental study into single-longitudinal-mode Tm, Ho:YVO4 lasers. (November 2015) - Dai, Tong-Yu; Han, Liu; Yao, Bao-Quan; Ju, You-Lun; Yu, Kuai-Kuai; Wang, Yue-Zhu
Abstract: The single-longitudinal-mode (SLM) Tm, Ho:YVO4 lasers were achieved by microchip configuration and double Fabry–Perot structure at room temperature. In the case of the microchip configuration laser, the maximum SLM power up to 17 mW was obtained on 2052.4 nm at 15 °C. In order to improve the output power of the SLM laser, it was implemented that the configuration of double Fabry-Perot etalons was used into the study of Tm, Ho:YVO4 lasers. Utilizing such configuration, the laser generated up to 95 mW output power in SLM at the wavelength of 2051.3 nm. With the angle of the Fabry–Perot etalons varied, the wavelength of the SLM laser could be turned from 2050.4 nm to 2051.3 nm, corresponding to a turning frequency of −64 GHz. Highlights: Achieved the maximum single-longitudinal-mode power of 17mW for the microchip configuration Tm, Ho:YVO4 laser. Obtained 95mW output power in single-longitudinal-mode for the double Fabry–Perot structure Tm, Ho:YVO4 laser. The wavelength turning frequency of 64GHz for the double Fabry–Perot structure.